Co-evolution and Sustainable Procurement in Humanitarian Organizations: The Mediating effect of Self-organization - Aryatwijuka, Wilbroad; Arimpa, Joan Shina; Mutebi, Henry; Tukamuhabwa, Benjamin; Muhwezi, Moses (American Journal of Supply Chain Management, 2024)
The study examined the role of self-organization in facilitating coevolution and sustainable procurement in Humanitarian Organisations (HOs). Materials and Methods: Using simple random sampling, data were collected from 79 Hos with respondents purposively selected following a quantitative cross-sectional design, which was analyzed through partial least structural equation modelling (PLS-SEM) using SmartPLS version 4.0.9.0. Findings: Co-evolution and self-organization play a significant role in the attainment of sustainable procurement, and the relationship between co-evolution and sustainable Procurement is partially mediated by self-organization. Implications to Theory, Practice and Policy: Co-evolutionary and self-organizing approach are introduced to allow humanitarian agencies procure sustainably during relief operations. HO procurement functions can interact with other partners in their procurement activities by continuously engaging each other and sharing resources. By confirming mediation, the mediation role of self-organization in the relationship between co-evolution and sustainable procurement among HOs, the study provides critical insights in the evolving literature. The study shows that co-evolution connects with self-organization and sustainable procurement. Furthermore, it explains how self-organization mediates the relationship between co-evolution and sustainable procurement.
Keywords: Co-Evolution; Self Organization; Sustainable Procurement; Humanitarian Organizations; Complex Adaptive System